PENGARUH FAKTOR INTERNAL PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - ANGGITA TRI RAHAYU; ADE HANIFA PUTRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to analyze the influence of internal company factors on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. The internal factors examined in this research include return on assets, firm size, thin capitalization, audit committee, independent commissioner and capital intensity. The data collection process in this study employed a quantitative approach. The sample was selected using a purposive sampling technique. Based on the established criteria, a total of 116 companies met the requirements for observation during the 2022-2024 period, and 348 data points were used for analysis. Hypothesis testing was conducted using multiple regression analysis. The results of the research indicate that return on assets and firm size have a significant influence on tax avoidance. This suggests that return on assets and firm size contribute to the company’s engagement in tax avoidance. Meanwhile, thin capitalization, audit committee, independent commissioner, and capital intensity were found to have no significant impact on tax avoidance.